2014
DOI: 10.1098/rsta.2014.0020
|View full text |Cite
|
Sign up to set email alerts
|

Temporal localized structures in photonic crystal fibre resonators and their spontaneous symmetry-breaking instability

Abstract: We investigate analytically and numerically the formation of temporal localized structures (TLSs) in an all photonic crystal fibre resonator. These dissipative structures consist of isolated or randomly distributed peaks in a uniform background of the intensity profile. The number of peaks and their temporal distribution are determined solely by the initial conditions. They exhibit multistability behaviour for a finite range of parameters. A weakly nonlinear analysis is performed in the neighbourhood of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…We have described spatially localized structures, recent investigations have shown that temporal localized structures have been found in fibre resonators [104,90,105,106,107,108] and in VCSELS with a saturable absorber [109]. On the other hand, it has been shown that the combinated influence of diffraction and chromatic dispersion leads to the formation of three dimensional localized structures often called light bullet [110,111,112,113].…”
Section: Discussionmentioning
confidence: 99%
“…We have described spatially localized structures, recent investigations have shown that temporal localized structures have been found in fibre resonators [104,90,105,106,107,108] and in VCSELS with a saturable absorber [109]. On the other hand, it has been shown that the combinated influence of diffraction and chromatic dispersion leads to the formation of three dimensional localized structures often called light bullet [110,111,112,113].…”
Section: Discussionmentioning
confidence: 99%
“…to have a finite domain of existence delimited by two pump power values [10], as well as to stabilize dark temporal LSs [11][12][13]. In the absence of fourth order dispersion, with only second or/and third orders of dispersion, fronts interaction leads to the formation of moving LS in a regime far from any modulational instability [14].…”
Section: Driving Fieldmentioning
confidence: 99%
“…The nonlinear Schrödinger equation supplemented by the cavity boundary condition leads to a generalized Lugiato-Lefever equation [10]. The inclusion of the fourth order dispersion allows the modulational instability (MI) to have a finite domain of existence delimited by two pump power values [10], as well as to stabilize dark temporal LSs [11][12][13]. In the absence of fourth order dispersion, with only second or/and third orders of dispersion, fronts interaction leads to the formation of moving LS in a regime far from any modulational instability [14].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental investigation of this radiation induced by the high order dispersion was carried out in [13,14]. Numerical studies on CSs bound states in the presence of high order dispersions have been reported in [15,[17][18][19][20][21][22].In this letter, we provide an analytical description of how two CSs can interact under the action of the Cherenkov radiation induced by high order dispersion. For this purpose, we use the paradigmatic Lugiato-Lefever model with the third order dispersion term.…”
mentioning
confidence: 99%
“…Experimental investigation of this radiation induced by the high order dispersion was carried out in [13,14]. Numerical studies on CSs bound states in the presence of high order dispersions have been reported in [15,[17][18][19][20][21][22].…”
mentioning
confidence: 99%